202 A new model for translating research to policy: the consortium for evidence-based policy. (1st September 2016) - Frattaroli, Shannon; Horwitz, Joshua; McGinty, E Beth; Gielen, Andrea C
Abstract : Background: Effective and promising policy interventions exist for many injury problems. There is a need for strategies to communicate more effectively with policymakers about the evidence base that supports injury prevention policy interventions. Description of the Problem: Despite a growing evidence-base of effective injury prevention policies, translating and disseminating effective interventions to policymakers remains a challenge. As a result, the reach and impact of the injury prevention field is limited. Results: The consortium model for evidence-based policy is a response to this need. The consortium process involves bringing together experts representing stakeholder interests (including researchers, advocates, and practitioners) from different disciplinary backgrounds to review the evidence about a topic, identifying areas of consensus that support policy recommendations, and disseminating the findings and recommendations to policymakers through multiple channels. To date we have engaged in three consortium initiatives on: 1) mental health and gun violence; 2) smoke alarms and residential fires; and 3) prescription drug overdose. The three initiatives are at different stages in the consortium process. Effective dissemination of the findings and recommendations from the mental health and gun violence initiative has resulted in policy change at the national and state levels in the United States. Reports from the smoke alarm and prescription drug efforts have been released and plans for dissemination to policymakers are underway. Conclusions: The consortium model for engaging researchers, advocates, and practitioners in translating the evidence on a particular topic into policy recommendations and disseminating those recommendations to policymakers is a promising approach. Lessons learned from across the three initiatives include how to effectively: 1) identify and engage participants in the consortium process; 2) produce findings and recommendations that will engage a policy response; and 3) respond to policymaker interest in the consortium's work. Opportunities to adapt and replicate this model in countries other that the United States should be pursued.